Efektivitas Fitur Kontrol Dalam Sistem Informasi Akuntansi Untuk Pengendalian Fraud Pada UMKM Digital - Annisa Ayu Dwi Pradipta; Mila Dewi Lufiana; Larasati Kusuma Putri; Ety Meikhati (Proceedings Law, Accounting, Business, Economics and Language, 2025)
This study aims to evaluate the effectiveness of three control features in Accounting Information Systems (AIS)—namely audit trail, access control, and anomaly detection—in mitigating fraud within digital-based micro, small, and medium enterprises (MSMEs). These features play a crucial role in building a secure, transparent, and adaptive financial system that responds to changes in transactional behavior. The audit trail records all activities chronologically and immutably; access control restricts access rights based on user roles; while anomaly detection identifies suspicious transactions with the support of artificial intelligence. The findings indicate that although all three features are effective, the audit trail is more easily implemented in MSMEs due to its technical simplicity and its contribution to enhancing accountability. The integration of these features is considered capable of creating a more effective, optimal and accurate fraud control system for digital-based MSMEs.